Dakwah Ustadz Hanan Attaki di TikTok: Efektik atau Sekedar Konten? - Iqbal, Muhammad (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
This study aims to analyze the effectiveness of Ustad Hanan Attaki's da'wah through the TikTok social media platform. Additionally, this abstract explains the research methods and theories used, namely literature review with the Stimulus-Organism-Response (S-O-R) theory and the concept of diffusion of innovation, as well as TikTok's relevance as a contemporary da'wah medium. Finally, the summary of findings indicates that Ustad Hanan Attaki's da'wah strategy on TikTok leverages the platform's characteristics to reach young audiences with relevant messages and an adaptive communication style. The results suggest that da'wah on TikTok has significant potential to increase religious awareness and is not merely entertainment content, despite challenges in delivering in-depth messages. Overall, this study provides a comprehensive understanding of TikTok's role in digital da'wah, especially among Generation Z and millennials. Keywords : preaching; Tiktok; generation Z, religious behavior; Hanan Attaki